2013
DOI: 10.1002/jgrg.20068
|View full text |Cite
|
Sign up to set email alerts
|

A coupled model of the global cycles of carbonyl sulfide and CO2: A possible new window on the carbon cycle

Abstract: [1] Carbonyl sulfide (COS) is an atmospheric trace gas that participates in some key reactions of the carbon cycle and thus holds great promise for studies of carbon cycle processes. Global monitoring networks and atmospheric sampling programs provide concurrent data on COS and CO 2 concentrations in the free troposphere and atmospheric boundary layer over vegetated areas. Here we present a modeling framework for interpreting these data and illustrate what COS measurements might tell us about carbon cycle proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
508
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(541 citation statements)
references
References 55 publications
(89 reference statements)
31
508
2
Order By: Relevance
“…A monthly mean of TES OCS results from June 2006 was published in Kuai et al (2015), which further validated the concept that direct ocean emissions of OCS are much greater than previously thought (Berry et al, 2013). The published data included retrievals over the ocean around ±40…”
Section: Previous Estimates From Satellitesupporting
confidence: 57%
See 1 more Smart Citation
“…A monthly mean of TES OCS results from June 2006 was published in Kuai et al (2015), which further validated the concept that direct ocean emissions of OCS are much greater than previously thought (Berry et al, 2013). The published data included retrievals over the ocean around ±40…”
Section: Previous Estimates From Satellitesupporting
confidence: 57%
“…Ingestion of OCS via leaf uptake only goes one way, meaning, plants do not respire OCS as they do unused CO 2 . Since OCS is roughly 4 times more variable than CO 2 , Berry et al (2013) suggested that remote detection of OCS could be used as a proxy towards estimating CO 2 fluxes over areas of dense vegetation. The remaining portion of the OCS sink budget is atmospheric loss due to reaction with the OH − and O − radicals along with stratospheric photolysis (Kettle et al, 2002).…”
Section: Sources and Sinksmentioning
confidence: 99%
“…It has a greenhouse gas effect based on absorption of far-infrared radiation (Brühl et al, 2012). OCS is also found as a potential trace gas, other than carbon dioxide, that could provide independent information about carbon cycle processes (Montzka et al, 2007;Campbell et al, 2008;Suntharalingam et al, 2008;Wohlfahrt et al, 2012;Blonquist et al, 2011;Berry et al, 2013). For example, recent work by Campbell et al (2008) suggests that carbonyl sulfide is a good photosynthetic tracer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies considering the large-scale atmospheric variability of OCS have linked OCS fluxes and the photosynthetic uptake of CO 2 for regional and global scales (1,4,13). Leaf-scale studies have confirmed the OCS link to photosynthesis (14,15).…”
mentioning
confidence: 97%
“…7 and 8). The terrestrial biosphere is the largest sink for OCS (1,4,9,10) with uptake by both oxic soils (e.g., ref. 11) and vegetation (e.g., ref.…”
mentioning
confidence: 99%